Bone mineral density in patients with end-stage renal disease and its evolution after kidney transplantation - Govindarajan, S. (Medknow Publications, 2011)
Renal transplantation is associated with abnormalities of the structure and function of the musculoskeletal system. No data are available on bone health in Indian patients with end-stage renal disease (ESRD) and its evolution after transplantation. Consecutive ESRD patients who underwent living donor renal transplantation were studied prospectively. Bone mineral density (BMD) was measured at lumbar vertebrae using quantitative computed tomography (CT) scan before transplantation and after 3 and 6 months. T and Z scores were calculated by comparing with normal control data, and values were correlated with various clinical and biochemical parameters. Of the 56 patients enrolled (mean age, 33.7 years; 47 males), 40 completed the 6-month follow-up. The vertebral trabecular bone density at the time of transplantation was 172±53 mg/cc and the average Z score was 0.26±1.7. There was a significant decline in BMD at 3 months (11.8%; P<0.0001) and 6 months (16%; P<0.0001) after transplantation. Both T and Z scores showed a significant decline at 3 and 6 months. There was a significant decline in intact parathormone (iPTH) levels after transplantation, but 15 (37.5%) patients continued to have raised iPTH 6 months after transplantation. The iPTH levels at 6 months had significant correlation with BMD decline (r=0.43, P=0.006). We conclude that Indian ESRD patients have relatively well-preserved BMD, but the density declines rapidly after transplantation. A significant proportion of patients exhibit persistent hyperparathyroidism 6 months after transplantation, which correlates with bone loss.